Preshcool teachers' knowledge of early childhood development and educational practices in Metropolitan Dhaka, Bangladesh - Momen, Tahima (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2010.